Nurses’ role in oral healthcare: a descriptive-analytical cross-sectional study in northeastern Iran - Mohammadreza Askari; Mohammad Rahimkhani; Masoud Abdollahi; Ali Mohammadabadi; Hamideh Yaghoobi; Mohammad Namazinia (BMC Oral Health)
Abstract Background Oral health is a vital component of overall health, particularly for hospitalized patients who are at higher risk of oral complications due to factors such as reduced salivary flow, medication side effects, and limited mobility. Nurses play a critical role in providing oral healthcare, yet studies indicate gaps in their knowledge, attitudes, and practices (KAP) in this area. This study aimed to evaluate the KAP of nurses regarding oral healthcare for hospitalized patients in northeastern Iran, a region with limited healthcare resources. Methods A cross-sectional study was conducted in 2023 among 112 nurses working in three hospitals in Torbat Heydarieh, northeastern Iran. Data were collected over a two-month period using a convenience sampling method and a validated questionnaire assessing knowledge (11 items), attitudes (16 items), and practices (8 items). The questionnaire underwent face and content validation, and its reliability was confirmed through a pilot study (Cronbach's alpha > 0.8). Data were analyzed using SPSS version 16, with descriptive statistics, chi-square tests, and correlation analysis. Results The mean scores for knowledge, attitudes, and practices were 7.01 ± 1.47 (out of 11), 31.58 ± 4.93 (out of 80), and 4.31 ± 1.05 (out of 8), respectively. Significant correlations were found between knowledge and attitudes (r = 0.279, p < 0.01) and attitudes and practices (r = 0.149, p < 0.01). Nurses with higher education levels and more work experience demonstrated better knowledge and attitudes, though these did not always translate into improved practices. Male nurses had significantly higher knowledge scores than female nurses (p = 0.021). Conclusions The study highlights moderate knowledge, positive attitudes, and suboptimal practices among nurses regarding oral healthcare. The weak correlation between knowledge, attitudes, and practices suggests that improving oral healthcare requires not only education but also institutional support and resource availability. Given the relatively limited sample size and the use of convenience sampling, caution is advised when generalizing these findings to other populations. Targeted training programs, interdisciplinary collaboration, and systemic changes are recommended to enhance oral healthcare practices in hospitals. Trial registration Not applicable.